Porous Metal–Organic Framework@Polymer Beads for Iodine Capture and Recovery Using a Gas‐Sparged Column. (5th June 2018) - Valizadeh, Bardiya; Nguyen, Tu N.; Smit, Berend; Stylianou, Kyriakos C.
Abstract: Iodine (I2 ) capture and recovery is an important process in many industrial practices. Conventional materials for I2 capture include Ag 0 ‐based aerogels and zeolites and C‐based aerogels and powders, which suffer from expensive and/or inefficient recovery. Recently, metal–organic frameworks (MOFs) have shown potential as good adsorbents for I2 capture with high capacity, fast uptake, and good recyclability. The powder form of MOFs, however, often makes them impractical in large‐scale applications. Herein, a versatile method based on the phase inversion technique is presented to fabricate millimeter‐sized spherical MOF@polymer composite beads, and the use of these beads for I2 capture and recovery is demonstrated. Besides preserving the crystallinity and pore accessibility of the embedded MOFs in the polymeric matrix, the beads exhibit higher capacity and faster uptake rate for I2 in both vapor and liquid phases compared to the bulk MOF powder. In order to showcase the applicability of these beads, a gas‐sparged column is used as a proof‐of‐concept device that can efficiently capture and recover more than 99% of I2 from the feeding solution. The beads can be recycled and reused multiple times, which in combination with their easy handling and storage highlights their superiority compared to MOF powders in adsorption applications. Abstract : Powders versus Beads . Using powders in industrial applications is often impractical. In this work, the phase inversion technique is utilized to shape metal–organic framework (MOF) powders into millimeter‐sized MOF    polymer beads. It is revealed that the beads can outperform MOF powders as they can efficiently capture iodine, be rapidly regenerated and reused for several cycles.